2019
DOI: 10.5539/ies.v12n5p109
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electronic Tests on Students’ Performance Assessment

Abstract: This study has aimed to measure the effect of electronic tests on the academic achievements of middle school students in Arabic course. The sample has been divided into two groups; the experimental group and the non-experimental group after using the mixed experimental method. Statistical measurements had been used before, and after, the experiment for both groups; whereas, study tools were consisted of achievements test and focus group. The results have assured the existence of statistical differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…This was probably due to the fact that they sat for the tests at home, where they could use course materials or be in contact with other learners. Scientific literature also mentions better results in electronic tests (Alyahya & Almutairi, 2019;Washburn et al, 2017). However, this paper is about the comparison of results from two different tests (in the winter and summer semester) at two different places (at school and at home), so it cannot be compared to other authors' experimental research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was probably due to the fact that they sat for the tests at home, where they could use course materials or be in contact with other learners. Scientific literature also mentions better results in electronic tests (Alyahya & Almutairi, 2019;Washburn et al, 2017). However, this paper is about the comparison of results from two different tests (in the winter and summer semester) at two different places (at school and at home), so it cannot be compared to other authors' experimental research.…”
Section: Resultsmentioning
confidence: 99%
“…There was no such stress at home, and I was able to concentrate better." On the contrary, the stress factor has been studied by some authors (Alyahya & Almutairi, 2019;Kolagari et al, 2018;Washburn et al, 2017) who have come to the conclusion that electronic tests increase students' anxiety more than paper tests. However, in this study the electronic tests took place in home environment, which, on the contrary, had a calming effect on the students.…”
Section: Computer Vs Paper Testsmentioning
confidence: 99%
“…Majorly, the three types of assessment used by educators to gauge students' learning outcomes from the beginning of the learning process to the end are categorized into diagnostic, formative, or summative assessments [34]. Categorically, diagnostic assessment is the beginning of the learning process assessment that helps in identifying the students' current knowledge, skill, and capabilities; formative assessment is an ongoing assessment that provides feedback and information as learning is taking place while summative assessment sums up the teaching and learning process which comes either at the end of a module, semester, study year or educational program [4,5,20,34,65].…”
Section: Introductionmentioning
confidence: 99%
“…Test anxiety is a combination of physiological over-arousal, tension, and somatic symptoms, along with worry, dread, fear of failure, and catastrophizing, which occur before or during test situations ( Zeidner, 1998 ). Technological changes and environmental factors such as a general decrease in an individual’s quality of life may affect test anxiety levels ( Alyahya and Almutairi, 2019 ; Chalutz Ben-Gal, 2020 ). Several test anxiety treatments have been assessed and reviewed, using various performance outcomes ( Tryon, 1980 ).…”
Section: Introductionmentioning
confidence: 99%
“…These interventions also include contemplative practices such as yoga, journaling ( Ergas, 2014 ), and mindfulness ( Praissman, 2008 ; Tarrasch, 2015 ; Garrison, 2017 ). Such programs help in supporting students with a variety of challenges as for example learning disabilities and test anxiety ( Vaughn et al, 2015 ; Mitchell and Gansemer-Topf, 2016 ; von der Embse et al, 2018 ; Alyahya and Almutairi, 2019 ). A recent study among higher education students compared two non-pharmacological interventions: mindfulness and device-guided slow breathing, and found that both interventions led to stress reduction ( Gabriely et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%